Verba Berprefiks Ber- pada Buku Cerita Anak: Kajian Proses Afiksasi - Shakti, Zasqia Damai Aulia; Kesuma, Tri Mastoyo Jati (Universitas Negeri Surabaya, 2024)
Children's storybooks play a crucial role in children's language development, thus demanding meticulous attention from authors in word selection and usage within the narrative. A comprehensive understanding of the morphological processes, particularly affixation, is essential for grasping the writing style. This study focuses on scrutinizing the morphological processes, particularly affixation, specifically the prefix ‘ber-’, on verbs. The analysis centers on the fundamental form and semantic formation. The dataset comprises all verbs prefixed with ber- sourced from a children's storybook titled